Orthogonal Array Testing Strategy (OATS) Technique Jeremy H. Harrel A Literature Review - Wuisan, Dewi (Indonesian Marketing Journal, 2024)
Knowledge about experimental design is mostly done in agriculture or animal husbandry, it is still rarely done in other fields, especially in marketing. However, experimental design research was then carried out in the industrial field, and some has also been done for marketing. Orthogonal Array (OA) is one part of a group of experiments that only use part of the total conditions, this part can be only half, a quarter or an eighth of a full factorial experiment. It can be said that Orthogonal arrays are used to design efficient experiments and analyze experimental data by using only part of the total conditions so that in this case it minimizes the number of experiments, where the number of experiments will be able to provide as much information as possible about the influencing factors. This discussion will also discuss how to use Orthogonal Array in research on industrial products. The use of experimental design which continues to develop will later be very useful in marketing to see how a product is desired by consumers and can make the resulting product better and can save costs so that the use of this experimental design research can be used in decision making for the use of a product of goods and services.